A virtual histology intravascular ultrasound analysis of coronary chronic total occlusions. Issue 3 (29th March 2012) - Guo, Jun; Maehara, Akiko; Mintz, Gary S; Ashida, Kazuhiro; Pu, Jun; Shang, Yunpeng; Leon, Martin B.; Stone, Gregg W.; Moses, Jeffrey W.; Ochiai, Masahiko
<x xml:space="preserve">Abstract</x> Objectives We used virtual histology intravascular ultrasound (VH‐IVUS) to investigate plaque composition of chronic total occlusions (CTO). Background There are limited data on the composition of CTOs, especially in vivo. Methods VH‐IVUS was performed in 50 CTO lesions (49 patients) after guidewire crossing or pre‐dilation using a 1.5–2 mm balloon. Plaque composition in the proximal reference, distal reference, and CTO segment (subsequently divided into proximal, middle, and distal subsegments) was analyzed and reported as median and interquartile range. VH‐IVUS phenotype was also assessed. The definition of a fibroatheroma was >10% confluent necrotic core (NC) in more than three consecutive frames. Results Overall, the maximum NC within the CTO [35.5% (28.7, 44.3%)] was similar to the proximal reference [35.6% (24.1, 42.1%)] and greater than the distal reference [31.5% (22.6, 35.2%), P < 0.01]. There was no difference in maximum NC observed among proximal [31.4% (25.2, 10.4%)], middle [31.0% (23.3, 38.3%)], and distal CTO subsegments [30.4% (22.0, 39.5%)]. Overall, 42/50 CTOs contained a VH‐fibroathroma; and 8/50 did not. CTOs containing a VH‐fibroatheroma had more NC and dense calcium while CTOs not containing a fibroatheroma had more fibrotic and fibrofatty plaque. Importantly, 60.5% of VH‐fibroatheroma‐containing CTOs had a thin‐cap fibroatheroma (NC abutted to the lumen) in the proximal reference. Conclusions Using VH‐IVUS, CTO morphology can be divided into two patterns: (1) CTO with VH‐fibroatheroma or (2) CTO without VH‐fibroatheroma. This suggests two mechanisms of CTO formation—the majority evolving from acute coronary syndrome and thrombosis and the minority from atherosclerosis progression. © 2012 Wiley Periodicals, Inc.